The curve C has the equation ye ^(–2x) = 2x + y^2 . Find dy/dx in terms of x and y.


differentiate both side with respect to x : (dy/dx)e^(-2x)+y(-2e^(-2x)) = 2+2y(dy/dx)
rearrange it : (-2y+e^(-2x))(dy/dy) = 2 + 2ye^(-2x) ==> dy/dx = ( 2 + 2ye^(-2x) ) / ( -2y+e^(-2x) )

Answered by Jimmy C. Maths tutor

4814 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How can you find the coefficients of a monic quadratic when you know only one non-real root?


How would I differentiate cos(2x)/x^1/2


Find the x values for stationary points in the curve y=3sin(2x) for 0<x<180


How to transform graphs of functions?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences